KAJIAN BIBLIOMETRIK PLAYFUL LEARNING DAN MOTIVASI BELAJAR DI SEKOLAH DASAR: VISUALISASI DATA MENGGUNAKAN VOSVIEWER - Isti, Lailia Arditya; Sutikno, Sutikno (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The purpose of the study was to determine the development of scientific publication results on the application of playful learning and elementary school learning motivation. The method used in the study is an approach based on bibliometric analysis assisted by VOSviewer visualization. Data retrieval was carried out on the Scopus and Google Scholar databases with a range of 2015 to 2025. The search keywords used in the Scopus database are